Association of knowledge and practice of Tuberculosis infection prevention and control policies among health care personnel at a regional hospital, in Gauteng province of South Africa - Sikhethiwe Masuku; Steve Olorunju; Ramadimetja Shirley Mooa; Martie van der Walt; Mmapheko Doriccah Peu (Elsevier, 2023)
Background: Tuberculosis (TB) remains an occupational health risk among healthcare personnel (HCP) globally, with the risk of transmission present throughout healthcare settings. The presence of undiagnosed and untreated highly infectious patients poses a great risk to the HCP who are often the forefront healthcare providers of any epidemic. Genotypic analysis of infected HCP revealed similar strains to the ones identified from the patient profile of their facilities, suggestive of nosocomial transmission. The aim of the study was to determine healthcare personnel's knowledge and practices regarding protective wear on TB prevention in Gauteng province. Methods: A non-experimental descriptive quantitative survey was used for this study. The sample was a cohort of healthcare professionals from a selected regional hospital located in Gauteng province of South Africa. Ethical approval was obtained from the University of Pretoria and the Gauteng Provincial Department of Health. Data were collected using a self-administered structured questionnaire which was distributed to the different categories of HCP at the selected facility. All analysis was conducted using Stata 15 and p-values less than 0.05 were considered statistically significant. Results: Knowledge of infection control policies was not significantly associated with practice. However, knowledge was significantly associated with level of education. HCP with higher levels of education demonstrated good knowledge but poor practice. Conclusion and recommendations: Good knowledge of infection prevention and control policies did not result in good practice. Hence, strategies to create knowledge translation towards IPC practices among HCP need to be devised.